Randomized Study Comparing the Effect of Carbon Dioxide Insufflation on Veins Using 2 Types of Endoscopic and Open Vein Harvesting. Issue 5 (September 2017) - Krishnamoorthy, Bhuvaneswari; Critchley, William R.; Nair, Janesh; Malagon, Ignacio; Carey, John; Barnard, James B.; Waterworth, Paul D.; Venkateswaran, Rajamiyer V.; Fildes, James E.; Caress, Ann L.; Yonan, Nizar
Abstract : Objective: The aim of the study was to assess whether the use of carbon dioxide insufflation has any impact on integrity of long saphenous vein comparing 2 types of endoscopic vein harvesting and traditional open vein harvesting. Methods: A total of 301 patients were prospectively randomized into 3 groups. Group 1 control arm of open vein harvesting (n = 101), group 2 closed tunnel (carbon dioxide) endoscopic vein harvesting (n = 100) and Group 3 open tunnel (carbon dioxide) endoscopic vein harvesting (open tunnel endoscopic vein harvesting) (n = 100). Each group was assessed to determine the systemic level of partial arterial carbon dioxide, end-tidal carbon dioxide, and pH. Three blood samples were obtained at baseline, 10 minutes after start of endoscopic vein harvesting, and 10 minutes after the vein was retrieved. Vein samples were taken immediately after vein harvesting without further surgical handling to measure the histological level of endothelial damage. A modified validated endothelial scoring system was used to compare the extent of endothelial stretching and detachment. Results: The level of end-tidal carbon dioxide was maintained in the open tunnel endoscopic vein harvesting and open vein harvesting groups but increased significantly in the closed tunnel endoscopic vein harvesting group ( P = 0.451, P = 0.385, and P < 0.001). Interestingly, partial arterial carbon dioxide also did not differ over time in the open tunnel endoscopic vein harvesting group ( P = 0.241), whereas partial arterial carbon dioxide reduced significantly over time in the open vein harvesting group ( P = 0.001). A profound increase in partial arterial carbon dioxide was observed in the closed tunnel endoscopic vein harvesting group ( P < 0.001). Consistent with these patterns, only the closed tunnel endoscopic vein harvesting group demonstrated a sudden drop in pH over time ( P < 0.001), whereas pH remained stable for both open tunnel endoscopic vein harvesting and open vein harvesting groups ( P = 0.105 and P = 0.869, respectively). Endothelial integrity was better preserved in the open vein harvesting group compared with open tunnel endoscopic vein harvesting or closed tunnel endoscopic vein harvesting groups ( P = 0.012) and was not affected by changes in carbon dioxide or low pH. Significantly greater stretching of the endothelium was observed in the open tunnel endoscopic open tunnel endoscopic vein harvesting group compared with the other groups ( P = 0.003). Conclusions: This study demonstrated that the different vein harvesting techniques impact on endothelial integrity; however, this does not seem to be related to the increase in systemic absorption of carbon dioxide or to the pressurized endoscopic tunnel. The open tunnel endoscopic harvesting technique vein had more endothelial stretching compared with the closed tunnel endoscopic technique; this may be due to manual dissection of the vein. Further research is required to evaluate the long-term clinical outcome of these vein grafts.